Stiffness measurement is a biomarker of skin ageing in vivo. Issue 12 (12th October 2020) - Runel, Gaël; Cario, Muriel; Lopez‐Ramirez, Noémie; Malbouyres, Marilyne; Ruggiero, Florence; Bernard, Laure; Puisieux, Alain; Caramel, Julie; Chlasta, Julien; Masse, Ingrid
Abstract: Human skin is particularly vulnerable to age‐related deterioration and undergoes profound structural and functional changes, reflected in the external skin appearance. Skin ageing is characterized by features such as wrinkling or loss of elasticity. Even if research advances have been done concerning the molecular mechanisms that underlie these changes, very few studies have been conducted concerning the structure stiffness of the skin organ as a whole. In this study, we showed, thanks to human skin reconstructs and the Japanese Medaka fish model, that biomechanics is a new biomarker of skin ageing. We revealed that global stiffness measurement by Atomic Force Microscopy, since modulated through ageing in these models, can be a new biomarker of skin ageing, and reflects the profound reorganization of the dermis extracellular matrix, as shown by Transmission Electron Microscopy. Moreover, our data unveiled that the Japanese Medaka fish could represent a highly relevant integrated model to study skin ageing in vivo.